The Architect of Prophecy: A Literary Analysis of Lady Jessica’s Religious Engineering in the Dune: Part Two Screenplay - Salamun (LITERA KULTURA : Journal of Literary and Cultural Studies, 2025)
This research explores the mechanisms of "Religious Engineering" executed by Lady Jessica in the screenplay of Dune: Part Two by Denis Villeneuve and Jon Spaihts. While the narrative often focuses on Paul Atreides’ journey as the "Lisan al-Gaib," this study posits that his messianic status is a calculated political construct orchestrated by Lady Jessica. Utilizing a qualitative literary analysis with a focus on political dramaturgy and discourse analysis, the study examines key scenes and dialogues that reveal how Jessica hijacks indigenous Fremen spirituality to secure the hegemony of House Atreides. The findings identify four primary strategic pillars: the utilization of ritual as a tool for spiritual legitimacy, the strategic collaboration with her unborn daughter (Alia) as a "coalition partner," the geopolitical exploitation of Southern fundamentalism, and the manipulation of psychological confirmation bias in local leadership. Furthermore, this research highlights the antithesis provided by the character Chani, whose resistance exposes the "Missionaria Protectiva" as a form of colonial epistemic violence. Ultimately, this analysis concludes that religion in the Dune universe serves as a weaponized alien invention, where the "Holy War" is not a spontaneous religious awakening, but a controlled demolition of indigenous agency designed for political survival.